A conserved family of elav-like genes in vertebrates. - Good, P J (1995)
A large family of genes encodes proteins with RNA recognition motifs that are presumed to bind RNA and to function in posttranscriptional regulation. Neural-specific members of this family include elav, a gene required for correct differentiation and maintenance of neurons in Drosophila melanogaster, and a related gene, HuD, which is expressed in human neuronal cells. I have identified genes related to elav and HuD in Xenopus laevis, zebrafish, and mouse that define a family of four closely related vertebrate elav-like genes (elrA, elrB, elrC, and elrD) in fish, frogs, and mammals. In addition to protein sequence conservation, a segment of the 3'-untranslated sequence of elrD is also conserved, implying a functional role in elrD expression. In adult frogs, elrC and elrD are exclusively expressed in the brain, whereas elrB is expressed in brain, testis, and ovary. During Xenopus development, elrC and elrD RNAs are detected by late gastrula and late neurula stages, respectively, whereas a nervous system-specific elrB RNA species is expressed by early tadpole stage. Additional elrB transcripts are detected in the ovary and early embryo, demonstrating a maternal supply of mRNA and possibly of protein. These expression patterns suggest a role for different elav-like genes in early development and neuronal differentiation. Surprisingly, elrA is expressed in all adult tissues tested and at all times during development. Thus, the widely expressed elrA is expected to have a related function in all cells.